FAKTOR KEPERCAYAAN, GETOK TULAR, KUALITAS YANG DIPERSEPSI, KESADARAN MEREK SISWA SMA JAKARTA TERHADAP UNIVERSITAS XXX - Rudy Santosa Sudirga (Journal of Business & Applied Management, 2016)
Evaluation factors which include trust, word of mouth, perceived quality, and brand awareness areimportant in determining senior high school students‟ choice to study at University XXX. The researchaims at identifing factors that are most important and interesting for the senior high school students inmaking their choice. A stratified random sampling of 400 senior high school students were employedto evaluate the evaluation of factors. In addition this sudy also aims to determine why senior highschool students are interested in choosing University XXX. The Long term goal of this study is todetermine whether changes need to be made and alterations have to be decided both in policyregarding the effectiveness of academic factors or other factors. In addition it will also look at theeffectiveness measures of the academic promotion factor. For the marketing of University XXX, thisresearch contributes in determining the strategy and other relevant factors to recruit more senior highschool students to join University XXX.Keywords: Trust, Word of Mouth, Perceived Quality